Orbital Lymphangioma: Case Report and Management Paradigms - Roman, Alex; Bianchini, Larissa; Battistel, Bárbara; Franzoi Neto, Miguel; Schwingel, Daniela (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Lymphangioma is a rare congenital vascular malformation of the head and neck region isolated from the systemic circulation. It has a benign etiology, and represents 1–3% of all orbital tumors. These hamartomas often present in the pediatric population with a slightly female predilection. They have a lymphocytic composition, and may increase in size with episodes of viral infection, causing proptosis.Discussion The management of this lesion is controversial, hardly curative, and depends on the clinical presentation. The treatment options include partial surgical resection of the major cyst, needle aspiration, surgical debulking, systemic steroids, sildenafil, intralesional injection of the sclerosing agents, and local radiotherapy.Case Report In the present report, we describe an uncommon case of lymphangioma in a 6-year-old female who was first submitted to neurosurgery for tumor resection and received sildenafil therapy later, with promising results.Conclusion The treatment of orbital lymphangiomas remains a controversial topic, and the use of sildenafil along with needle aspiration and microsurgical removal is a viable option of treatment. However, many issues, such as the ideal duration of the therapy, the dosage regimen and the recurrence rate, still remain unclear. Our case report adds promising data on this pathology, even though larger trials are needed to properly elucidate the remaining questions.
Keywords: orbital lymphangioma; sildenafil; orbital tumors